European distance running and television ratings: a problem for world athletics - Barra, L. (New Studies in Athletics, 2007)
Whereas Europe once took 70% or more of the total medals on offer at the World Championships in Athletics and Olympic Games, it now takes 50% or less. The "lost" medals are mainly in the middle and long-distance races, where African runners now dominate and European performances have slipped. Coinciding with this change has been a dramatic drop in television viewing figures for major events in the European countries whose broadcasters provide the largest share of the income for both the IAAF and the Area association European Athletics. If the amount these broadcasters are will to pay for the rights to show future championships is reduced, it will compromise the funding for the operation and further development of the sport. The author, a highly experienced sport administrator, argues that the sport`s leaders need to take radical measures to improve the performance of European distance runners and outlines a `Marshall Plan` of eight suggestions.